Reflexión sobre los retos y amenazas éticas de la e-salud. - Mendoza Victoria, Luz Llined
The development of e-health is not only about the continuous evolution of a system that through technology generates new opportunities for health systems worldwide, this requires considering different aspects inherent to human interaction, that is because the objective of this document is to reflect on the different challenges and ethical threats of e-health and some of its most recognized components. In its development, the chronology of appearance of the different terms related to e-health, including its definition, is presented. In order to reflect on the ethical challenges and threats, a clinical case is developed as an example.